AB0834 CLINICAL CHARACTERISTICS OF PSORIATIC ARTHRITIS IN CHINESE PATIENTS: A CROSS‑SECTIONAL OBSERVATIONAL STUDY. (13th June 2020) - Song, Z.; Li, B.; Zhang, Z.
Abstract : Background: The clnical features of psoriatic arthritis(PsA)greatly varied in reports fomr different countries.There was no exact data in China. Objectives: To disclose the characteristics of PsA in China, we initiated an investigation it in our cohort of PsA patients. Methods: A cross-sectional observational study was conducted in our PsA cohort of Peking University First Hospital. All the clinical and imaging data at the patient's first visit were collected, including the age, gender, disease course, skin lesion, arthritis, dactylitis, enthesis, laboratory tests, concomitant diseases and so on. Results: Two hundred and seventy-nine patients with PsA were enrolled in this study. Their mean age was 41 year-old with 132 (47.3%) female. Median disease duration was 3 years. Among these patients, 196(73.4%)patients had the skin lesion first, 47 (17.6%)patients had the arthritis first, and the other 24(9.0%) patients had the psoriasis and the arthritis at the same time. Arthritis was the most common manifestation. Polyarthritis was the most common arthritic manifestation with proximal interphalangeal (PIP) joint as the most frequently involved joint. Dactylitis was observed in 89 (31.9%) patients, mostly at the second, third and fourth toe. Enthesis was found in 18 (6.5%) patients by physical examination, however, in 158 (56.5%) patients with the aid of ultrasound and MRI. Conclusion: Polyarthritis was the most common arthritis type in Chinese PsA patients, and PIP joint was the most involved joint, and the second, the middle and the fourth toe were the most frequently digits. The imaging techniques, especially ultrasound dramatically increased the identification of enthesis. References: [1]Ritchlin CT, Colbert RA, Gladman DD. Psoriatic arthritis. N Engl J Med 2017;376: 957–70. [2]Qing Yu Zeng, Ren Chen, John Darmawan et al. Rheumatic Diseases in China. Arthritis Research & Therapy Vol 10 No 1. Disclosure of Interests: None declared